2020
DOI: 10.1021/acs.chemmater.9b04437
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Ground-State Structure of BaZrO3 by Neutron Scattering Experiments and First-Principles Calculations

Abstract: The all-inorganic perovskite barium zirconate, BaZrO 3 , is a widely used material in a range of different technological applications. However, fundamental questions surrounding the crystal structure of BaZrO 3 , especially in regard to its ground-state structure, remain. While diffraction techniques indicate a cubic structure all the way down to T = 0 K, several first-principles phonon calculation studies based on density functional theory indicate an imaginary (unstable) phonon mode due to the appearance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 58 publications
13
52
0
Order By: Relevance
“…We obtain the ZPE-corrected lattice constant a ZPE and the ZPEcorrected vibrational frequencies ω ZPE , as well as temperature effects, within the QHA. As we have reported before [11], and is shown in Fig. 2, the vibrational frequency for the R 25 mode is very sensitive to the lattice constant.…”
Section: A Structure Stability and Thermal Expansionsupporting
confidence: 70%
See 4 more Smart Citations
“…We obtain the ZPE-corrected lattice constant a ZPE and the ZPEcorrected vibrational frequencies ω ZPE , as well as temperature effects, within the QHA. As we have reported before [11], and is shown in Fig. 2, the vibrational frequency for the R 25 mode is very sensitive to the lattice constant.…”
Section: A Structure Stability and Thermal Expansionsupporting
confidence: 70%
“…In that previous study [11], we also found that the PBE version of the GGA predicts the cubic phase down to T = 0, although the R 25 mode is significantly softer in PBE. By taking the effect of vibrational zero-point energy (ZPE) into account, the raw DFT lattice constant a 0 was seen to increase by a ZPE = a ZPE − a 0 = 0.007 Å in PBE and CX0p.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations